2020
DOI: 10.1590/0037-8682-0249-2020
|View full text |Cite
|
Sign up to set email alerts
|

Coccidioidomycosis in a reference center in Northeast Brazil: clinical/epidemiological profile and most common radiological findings

Abstract: Introduction: Coccidioidomycosis, a disease caused by Coccidioides immitis or Coccidioides posadasii, is endemic in arid climatic regions in Northeast Brazil. Its prevalence is higher among young adult males living in rural areas. Existing literature about this disease in Ceará, a Northeast Brazilian state, are scarce. Here, we aimed to outline the clinical and epidemiological profiles, radiological patterns, and therapeutic responses of patients with coccidioidomycosis in a reference center in Ceará, Brazil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…On the other hand, this review showed that the incidence of coccidioidomycosis was higher in the male gender than the female gender. Also, the most affected age group was 31-40 years, which coincides with data reported in Argentina, Venezuela, Brazil, and Mexico [4,5,[98][99][100][101]. Likewise, the present work illustrated that the disseminated clinical form was the most predominant, mainly affecting cutaneous and subcutaneous tissue, the peritoneum, the CNS, and the bone system.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, this review showed that the incidence of coccidioidomycosis was higher in the male gender than the female gender. Also, the most affected age group was 31-40 years, which coincides with data reported in Argentina, Venezuela, Brazil, and Mexico [4,5,[98][99][100][101]. Likewise, the present work illustrated that the disseminated clinical form was the most predominant, mainly affecting cutaneous and subcutaneous tissue, the peritoneum, the CNS, and the bone system.…”
Section: Discussionsupporting
confidence: 90%
“…No Brasil, o primeiro caso de coccidioidomicose foi descrito em 1978, na Bahia, seguido por outro caso no Piauí em 1979. Desde então, várias ocorrências foram relatadas em outros estados nordestinos, região que se constitui na maior área endêmica do país atualmente (MORAIS et al, 2020).…”
Section: Desenvolvimentounclassified
“…In Brazil, CM occurs exclusively in the northeast region, where approximately 136 cases of the disease have been reported since 1978: 94 cases in the state of Piauí [ 61 ]; six cases in the state of Maranhão [ 18 , 61 , 62 ]; 30 cases in the state of Ceará [ 63 , 64 , 65 , 66 , 67 , 68 ]; two cases in the state of Bahia [ 55 , 68 ]; four cases in the state of Pernambuco [ 59 , 60 ] ( Figure 2 ).…”
Section: Coccidioidomycosis In Brazilmentioning
confidence: 99%
“…One patient developed pericarditis without pulmonary involvement [ 35 ]. Although there are no official clinical-epidemiological data, the scientific literature indicates that only two cases of acute pulmonary disease evolved to death, despite antifungal treatment [ 63 , 69 ]. Most patients were treated with deoxycolate amphotericin B and oral fluconazole; a minority of patients were treated with only one of these drugs alone.…”
Section: Coccidioidomycosis In Brazilmentioning
confidence: 99%